Visual scoring of non cavitated caries lesions and clinical trial efficiency, testing xylitol in caries‐active adults. Issue 3 (8th November 2013) - Brown, John P.; Amaechi, Bennett T.; Bader, James D.; Gilbert, Gregg H.; Makhija, Sonia K.; Lozano‐Pineda, Juanita; Leo, Michael C.; Chen, Chuhe; Vollmer, William M.; for the X‐ACT Trial Collaborative Group
Abstract Objectives To better understand the effectiveness of xylitol in caries prevention in adults and to attempt improved clinical trial efficiency. Methods As part of the Xylitol for Adult Caries Trial (X‐ACT), non cavitated and cavitated caries lesions were assessed in subjects who were experiencing the disease. The trial was a test of the effectiveness of 5 g/day of xylitol, consumed by dissolving in the mouth five 1 g lozenges spaced across each day, compared with a sucralose placebo. For this analysis, seeking trial efficiency, 538 subjects aged 21–80, with complete data for four dental examinations, were selected from the 691 randomized into the 3‐year trial, conducted at three sites. Acceptable inter‐ and intra‐examiner reliability before and during the trial was quantified using the kappa statistic. Results The mean annualized noncavitated plus cavitated lesion transition scores in coronal and root surfaces, from sound to carious favoured xylitol over placebo, during the three cumulative periods of 12, 24, and 33 months, but these clinically and statistically nonsignificant differences declined in magnitude over time. Restricting the present assessment to those subjects with a higher baseline lifetime caries experience showed possible but inconsistent benefit. Conclusions There was no clear and clinically relevant preventive effect of xylitol on caries in adults with adequate fluoride exposure when non cavitated plus cavitated lesions were assessed. This conformed to the X‐ACT trial result assessing cavitated lesions. Including non cavitated lesion assessment in this full‐scale, placebo‐controlled, multisite, randomized, double‐blinded clinical trial in adults experiencing dental caries did not achieve added trial efficiency or demonstrate practical benefit of xylitol. Trial Registration: ClinicalTrials.Gov NCT00393055.